Discovery and Early Clinical Development of LY3202626, a Low-Dose, CNS-Penetrant BACE Inhibitor - McKinzie, David L; Winneroski, Leonard L; Green, Steven J; Hembre, Erik J; Erickson, Jon A; Willis, Brian A; Monk, Scott A; Aluise, Christopher D; Baker, Thomas K; Lopez, Jose E; Hendle, Jörg; Beck, James P; et al. (Journal of medicinal chemistry, 2021)
The beta-site APP cleaving enzyme 1, known as BACE1, has been a widely pursued Alzheimer’s disease drug target owing to its critical role in the production of amyloid-beta. We have previously reported the clinical development of LY2811376 and LY2886721. LY2811376 advanced to Phase I before development was terminated due to nonclinical retinal toxicity. LY2886721 advanced to Phase II, but development was halted due to abnormally elevated liver enzymes. Herein, we report the discovery and clinical development of LY3202626, a highly potent, CNS-penetrant, and low-dose BACE inhibitor, which successfully addressed these key development challenges.